The Journey of Ni(I) Chemistry. Issue 12 (15th November 2021) - Bismuto, Alessandro; Finkelstein, Patrick; Müller, Patrick; Morandi, Bill
Abstract: In the last twenty years, nickel has successfully imprinted its role in the field of homogeneous catalysis as a valid and complementary alternative to palladium and platinum catalysts. However, compared to those, there are often many different available pathways in nickel catalysis due to the facile access of intermediate oxidation states. Among them, Ni(I) has been increasingly proposed as a key oxidation state in multiple transformations. This oxidation state had already been suggested a long time ago but has only recently undergone a renaissance with extensive ligand design which has led to over 100 isolated Ni(I) complexes. In addition, the analysis of many catalytic cycles has revealed that the Ni(I) species can not only occur as a decomposition product perturbing a Ni(0)–Ni(II) pathway but can also play a key role in alternative Ni(I)–Ni(III) cycles. This behavior is highly dependent on the class of transformation and ligand employed in catalysis. Herein, we concisely describe the journey of this oxidation state, combining the information gathered from inorganic synthesis and mechanistic investigations, from its synthesis to its postulated role in different catalytic cycles. Abstract :